Systematic Review of the Studies Examining the Impact of the Interactive Whiteboard on Teaching and Learning: what we do learn and what we do not - Kyriakou, Artemis; Higgins, Steve (Preschool and Primary Education, 2016)
This systematic review focuses on the impact of Interactive Whiteboards (IWBs) on teaching and learning. Learning is interpreted through a Vygotskian constructivist lens, emphasizing quality through dialogic interaction. Classroom interactions and achievement in standardized tests are considered formative and summative assessment tools, respectively. Thus, our aim was to investigate whether the IWB technology had any effect on teaching and learning, reflected in standardized forms of testing or in-classroom quality measures. An online search through Proquest and FirstSearch resulted in sixteen studies of diverse methodologies. Qualitative synthesis of quantitative data indicated that IWBs have not raised the levels of pupils’ achievement and do not necessarily impact the quality of classroom learning. More longitudinal studies should focus on particular subjects taught, the age of pupils and particular type(s) of use. Overall, quality teaching is an important condition for improved learning, which does not necessarily result from IWB use. However, there is a general consensus across all studies that learning can be facilitated and improved through the use of IWB. Synchronizing theory with technological applications seems to be key in answering such assumptions positively. More importantly, concerns are raised regarding the unfolded relation between achievement and classroom interaction.